Molecular characterization of a potential receptor of Eimeria acervulina microneme protein 3 from chicken duodenal epithelial cells - Zhang Zhenchao; Zhou Zhouyang; Huang Jianmei; Sun Xiaoting; Haseeb Muhammad; Ahmed Shakeel; Shah Muhammad Ali A.; Yan Ruofeng; Song Xiaokai; Xu Lixin; Li Xiangrui (Parasite, 2020)
Eimeria acervulina is one of seven Eimeria spp. that can infect chicken duodenal epithelial cells. Eimeria microneme protein 3 (MIC3) plays a vital role in the invasion of host epithelial tissue by the parasite. In this study, we found that chicken (Gallus gallus) ubiquitin conjugating enzyme E2F (UBE2F) could bind to the MIC3 protein of E. acervulina (EaMIC3), as screened using the yeast two-hybrid system, and that it might be the putative receptor protein of EaMIC3. The UBE2F gene was cloned from chicken duodenal epithelial cells. The recombinant protein of UBE2F (rUBE2F) was expressed in E. coli and the reactogenicity of rUBE2F was analyzed by Western blot. Gene sequencing revealed that the opening reading frame (ORF) of UBE2F was 558 base pairs and encoded a protein of 186 amino acids with a molecular weight of 20.46 kDa. The predicted UBE2F protein did not contain signal peptides or a transmembrane region, but had multiple O-glycosylation and phosphorylation sites. A phylogenetic analysis showed that the chicken UBE2F protein is closely related to those of quail and pigeon (Coturnix japonica and Columba livia). A sporozoite invasion-blocking assay showed that antisera against rUBE2F significantly inhibited the invasion of E. acervulina sporozoites in vitro. Animal experiments indicated that the antisera could significantly enhance average body weight gains and reduce mean lesion scores following a challenge with E. acervulina. These results therefore imply that the chicken UBE2F protein might be the target receptor molecule of EaMIC3 that is involved in E. acervulina invasion.